The Impact of Cash Transfers on School Enrollment : Evidence from Ecuador - Oosterbeek, Hessel; Ponce, Juan; Schady, Norbert (World Bank, Washington, DC, 2012)
This paper presents evidence about the impact on school enrollment of a program in Ecuador that gives cash transfers to the 40 percent poorest families. The evaluation design consists of a randomized experiment for families around the first quintile of the poverty index and of a regression discontinuity design for families around the second quintile of this index, which is the program's eligibility threshold. This allows us to compare results from two different credible identification methods, and to investigate whether the impact varies with families' poverty level. Around the first quintile of the poverty index the impact is positive while it is equal to zero around the second quintile. This suggests that for the poorest families the program lifts a credit constraint while this is not the case for families close to the eligibility threshold.